Choice overload in consumer services: The mediating role of decision strategy complexity on subjective states and behavioral outcomes - Alain Decrop; Giacomo Del Chiappa (Journal of Tourism, Heritage & Services Marketing, 2024)
Purpose: The contemporary retail landscape is marked by a vast array of products and information, presenting consumers with an increasing number of choices. This phenomenon, known as choice overload, often overwhelms individuals and leads them to abandon their purchase, delay their decision, or opt for simpler choices. This study contributes to the literature on choice overload by focusing on two services (i.e. hotels and telecommunication plans) and exploring the mediating role of decision strategy complexity on subjective states and behavioral outcomes.